THE ROLE OF FAIRY TALES IN THE TEACHING OF ENGLISH (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Nowadays there are many different ways to learn English. Each has its own merits and gives positive results. Some methods recommended for teaching pupils. However, there is a very interesting option, which well perceived by both adults and children. You can probably guess that English fairy tales are the most effective tool, with the help of which language learning becomes a fun activity. This aspect especially appreciated by the children’s audience.